2017
DOI: 10.4081/mr.2017.7288
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping of the Helicobacter pylori isolates of raw milk and traditional dairy products

Abstract: Notwithstanding the substantial clinical impact of Helicobacter pylori, its convinced routes of transmission and sources have not been reported. Based on the quarrelsome hypothesis, foods and especially dairy products play an authoritative role in the transmission of H. pylori to humans. The current investigation was done to study the prevalence rate and distribution of vacA genotypes in the H. pylori strains isolated from the raw milk and traditional dairy products. Three-hundred milk and dairy samples were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 20 publications
3
6
0
Order By: Relevance
“…Moreover, differences in the feed of ovine with bovine, buffalo, camel and even caprine species may affect the prevalence rate of bacteria presented in their milk. Higher prevalence of H. pylori in raw ovine milk was also reported by previous investigations [ 10 , 31 , 32 , 34 43 ]. Using thorns and thistles in deserts and living away from humans and the polluted environment of cities are the most important probable reasons for the lower prevalence of H. pylori in camel milk.…”
Section: Discussionsupporting
confidence: 86%
“…Moreover, differences in the feed of ovine with bovine, buffalo, camel and even caprine species may affect the prevalence rate of bacteria presented in their milk. Higher prevalence of H. pylori in raw ovine milk was also reported by previous investigations [ 10 , 31 , 32 , 34 43 ]. Using thorns and thistles in deserts and living away from humans and the polluted environment of cities are the most important probable reasons for the lower prevalence of H. pylori in camel milk.…”
Section: Discussionsupporting
confidence: 86%
“…Higher incidence of H. pylori in some kinds of dairy samples was also reported by previous investigations (Angelidis et al, 2011;Bianchini et al, 2015;Fujimura et al, 2002;Khaji, Banisharif, & Alavi, 2017;Mousavi et al, 2014;Osman et al, 2015;Quaglia et al, 2007;Quaglia et al, 2008;Rahimi & Kheirabadi, 2012;Safaei et al, 2011;Talaei et al, 2015;Talimkhani & Mashak, 2017;Zamani, Vahedi, Maghdouri, & Shokri-Shirvani, 2017). Reversely, lower incidence of H. pylori in some kinds of dairy samples was also reported by previous investigations (Esmaeiligoudarzi et al, 2015;Mousavi et al, 2014;Rahimi & Kheirabadi, 2012;Saeidi & Sheikhshahrokh, 2016).…”
Section: Incidence Of Helicobacter Pylori In Assessed Samplessupporting
confidence: 82%
“…High incidence of vacA , cagA , and iceA1 genotypes was also reported in the H. pylori strains isolated from clinical samples of human and animal species (Dabiri et al, ; Momtaz, Dabiri, Souod, & Gholami, ; Podzorski, Podzorski, Wuerth, & Tolia, ; Torkan & Shahreza, ). Furthermore, high incidence of these genotypes has been reported in the H. pylori strains isolated from different types of food samples (Esmaeiligoudarzi et al, ; Ghorbani et al, ; Gilani, Razavilar, Rokni, & Rahimi, ; Khaji et al, ; Mousavi et al, ; Ranjbar et al, 2016a, 2016b; Saeidi & Sheikhshahrokh, ; Talaei et al, ; Talimkhani & Mashak, ; Yahaghi et al, ). Adjacent association of vacA , cagA , and iceA genotypes of H. pylori bacteria with secretion of interleukin‐8 and cytotoxin, adhesion to gastric epithelial cells, occurrence of inflammatory effect, vacuolization, apoptosis procedure in gastric epithelial cells, peptic ulceration, increase acute neutrophilic infiltration, interleukin‐10 secretion and inflammation, has been presented previously (Dabiri et al, ; Podzorski et al, ; Torkan & Shahreza, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The boost incidence of vacA, cagA, iceA1, oipA, cagE and babA2 genotypes was also conveyed in the H. pylori bacteria recovered from clinical samples of human and animal species. 42,52,54 Khaji et al 55 conveyed that vacA s1a (91.66%), m1a (61.61%), s2 (36.66%), and m2 (31.66%) were the most generally perceived genotypes amongst the H. pylori bacteria recovered from raw milk of animal species. They also showed that s1am1a (41.66%), s2m1a (25%), 16%), s1a/cagA+/iceA1/oipA+ (10.81%), s1a/ cagA−/iceA1/oipA+ (10.81%), s1b/cagA+/iceA1/oipA− (9.45%), m2/cagA+/iceA1/oipA+ (9.45%), m2/cagA +/iceA1/oipA− (9.45%), m2/cagA−/iceA1/oipA+ (9.45%), and m2/cagA−/iceA1/oipA− (9.45%) combined genotypic patterns were the most generally perceived in the H. pylori bacteria recovered from ready to eat food.…”
Section: Combined Genotyping Patterns Distribution* (%)mentioning
confidence: 99%